Single-cell transcriptomics reveals skewed cellular communication and phenotypic shift in pulmonary artery remodeling - Slaven Crnkovic; Francesco Valzano; Elisabeth Fließer; Jürgen Gindlhuber; Helene Thekkekara Puthenparampil; Maria Basil; Mike P. Morley; Jeremy Katzen; Elisabeth Gschwandtner; Walter Klepetko; Edward Cantu; Heimo Wolinski; et al. (JCI Insight, 2022)
A central feature of progressive vascular remodeling is altered smooth muscle cell (SMC) homeostasis; however, the understanding of how different cell populations contribute to this process is limited. Here, we utilized single-cell RNA sequencing to provide insight into cellular composition changes within isolated pulmonary arteries (PAs) from pulmonary arterial hypertension and donor lungs. Our results revealed that remodeling skewed the balanced communication network between immune and structural cells, in particular SMCs. Comparative analysis with murine PAs showed that human PAs harbored heterogeneous SMC populations with an abundant intermediary cluster displaying a gradient transition between SMCs and adventitial fibroblasts. Transcriptionally distinct SMC populations were enriched in specific biological processes and could be differentiated into 4 major clusters: oxygen sensing (enriched in pericytes), contractile, synthetic, and fibroblast-like. End-stage remodeling was associated with phenotypic shift of preexisting SMC populations and accumulation of synthetic SMCs in neointima. Distinctly regulated genes in clusters built nonredundant regulatory hubs encompassing stress response and differentiation regulators. The current study provides a blueprint of cellular and molecular changes on a single-cell level that are defining the pathological vascular remodeling process.